PELAKSANAAN KEGIATAN BERMAIN KARTU UNTUK MENINGKATKAN KEMAMPUAN MENGENAL HURUF HIJAIYYAH DI RAUDHATUL ATHFAL DHARMA WANITA PERSATUAN KOTA JAMBI (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The introduction of Hijaiyyah letters is a fundamental skill that is important for early childhood as a foundation for reading the Qur'an. However, in the learning practice at RA Dharma Wanita Persatuan, Jambi City, several obstacles are still found, such as differences in children's abilities in recognizing letters, limited variation in learning media, and children's concentration that is not yet stable during learning activities. This research used a qualitative approach with a descriptive method. Data collection techniques were carried out through observation, interviews, and documentation. The research subjects included the school principal, classroom teachers, and children aged 5–6 years. The data obtained were then analyzed through data reduction, data display, and conclusion drawing. The results of the study showed that the Hijaiyyah letter card playing activities were carried out through planning, implementation, and evaluation stages. Teachers prepared media and learning activities that were adjusted to children's development, then introduced letters through matching card games, pronouncing letter sounds, and group games. This activity received a positive response because it made children more enthusiastic, active, and helped improve their ability to recognize Hijaiyyah letters. However, some children still experienced difficulties distinguishing letters with similar shapes, thus requiring further guidance. Supporting factors in the implementation of this activity included the availability of learning media, school support, and children's learning motivation, while inhibiting factors included differences in children's abilities, limited variation in learning media, and lack of concentration among some children.